2010
DOI: 10.1167/iovs.09-4550
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Expression of Matrix Metalloproteinase and Proinflammatory Cytokine Genes after Trichiasis Surgery

Abstract: PURPOSE. Trachoma, the leading infectious cause of blindness, is a chronic inflammatory scarring condition. Blindness follows the development of trichiasis, which is treated surgically. Unfortunately, it frequently recurs, compromising the treatment. In this study, gene expression analysis was used to examine factors that may be involved in the inflammation and tissue remodeling after surgery. METHODS. Subjects were examined before and at 1 and 4 years after surgery. Conjunctival swab samples were collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
5
34
1
Order By: Relevance
“…Matrix metalloproteinases are capable of degrading the protein components of the ECM and also have wide-ranging effects on inflammatory and immune responses (50,58). Previous studies have implicated MMPs in the pathogenesis of trachomatous scarring, and this was further confirmed in the present study in a separate population (9,10,14,20,29,44). MMP7, MMP9, MMP12, and TIMP1 were upregulated in scarring and inflammation, whereas MMP10 and SPARCL1 were downregulated.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Matrix metalloproteinases are capable of degrading the protein components of the ECM and also have wide-ranging effects on inflammatory and immune responses (50,58). Previous studies have implicated MMPs in the pathogenesis of trachomatous scarring, and this was further confirmed in the present study in a separate population (9,10,14,20,29,44). MMP7, MMP9, MMP12, and TIMP1 were upregulated in scarring and inflammation, whereas MMP10 and SPARCL1 were downregulated.…”
Section: Discussionsupporting
confidence: 83%
“…Infection with other bacteria was more frequent, and many of the genes described above involved in innate immunity showed moderate to large increases in expression if a pathogenic organism was present. A previous study found that the presence of bacterial infection was associated with increased expression of IL1B, TNF-␣, MMP1, MMP9, and TIMP2 after trichiasis surgery (10). In the present study, bacterial infection was also found to be associated with an increased inflammatory infiltrate and tissue edema with IVCM.…”
Section: Discussionsupporting
confidence: 74%
“…It is also likely that nonchlamydial bacterial infections stimulate the inflammatory response, especially where there is established tissue disruption caused by repeated C. trachomatis infection. (10) In addition to the epithelium, other cells, such as macrophages and neutrophils, probably contribute to the production of these proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of C. trachomatis infection in a monkey model demonstrated that after a primary infection the inflammatory phenotype could be induced by inoculating the conjunctiva with the C. trachomatis HSP60 antigen (66). There are some data on the immunological response in early active trachoma; however, there is limited information about the cicatricial stage (10,28,30,44,45). It is unknown which fibrogenic pathways are important to this disease process and what drives them.…”
Section: Differences In Conjunctival Gene Expression Profiles Betweenmentioning
confidence: 99%
See 1 more Smart Citation